AL-RAHNU DEVELOPMENT IN MALAYSIA: A CASE OF AL-RAHNU INSTITUTION UNDER THE TERENGGANU ISLAMIC RELIGIOUS AND MALAY CUSTOMS COUNCIL (International Journal of Islamic Business, 2019)
The presence of the Islamic pawn broking scheme (al-rahnu) has caught attention in Malaysia, and has encouraged participation by society, especially low-income groups. One of the objectives in implementing this scheme was to protect the society, especially the Muslim community, from transactions involving elements of interest (riba). Al-rahnu operates by offering cash loan facilities that are quick, fair, transparent, and is based on Syariah principles. By the implementation of the Islamic pawn broking scheme the government is hoping that this scheme will be the primary option and eventually will replace the conventional scheme for pawn broking services. Even though the conventional pawn scheme has existed in Malaysia for a long time, and has monopolized the industry, Islamic pawn broking scheme is getting a huge demand by the society. After twenty years of its implementation in Malaysia, al-rahnu has become an important instrument in economic development as customers who have really no access or capacity to receive loans from the banking system can obtain financing from al-rahnu within minutes. As such, this paper will discuss the background of Islamic pawnshops in Malaysia and will be followed by a discussion that is focused on the Islamic concept of the pawnshop based on fiqh. The operation, implementation and performance aspects of Islamic pawnshops are also mentioned in this study by referring to al-rahnu under Terengganu Islamic Religious and Malay Customs Council (MAIDAM), which was started in 1992 and was the first al-rahnu institution in Malaysia.